Application of Digital Marketing in Efforts to Empower Productive Communities and Preserve Banyuwangi Culture - Sulistyan, Riza Bahtiar; Carito, Danang Wikan; Cahyaningati, Retno; Muttaqien, Fauzan (International Journal of Public Devotion, 2023)
Technological developments in the form of implementing online sales are currently widely used by several MSMEs. But there are still many who still sell offline. Including what happened to one UMKM in Banyuwangi. The purpose of this activity is to introduce MSME products to the wider community without being bound by distance and time, increase the community's ability to use digital marketing, and increase sales. The method used includes the planning, implementation, and evaluation stages. Participants in this activity came from MSMEs in the Banyuwangi Papring Environment. Analysis of the results of activity evaluation is carried out using descriptive statistics and is measured using indicators of knowledge, understanding, and practical skills. The results of the analysis show that the existence of training and mentoring programs is very good and able to improve the abilities of the trainees. The increase was shown from the comparison before and after the activity, the increase included aspects of knowledge, understanding and practical skills. Training participants are able to operate the features in the digital marketing platform and are able to buy and sell online.